SL METAVERSE: MEDIA ANTHROPOLOGY - Serra Navarro, David (Design/Arts/Culture, 2023)
The metaverse that Neal Stephenson conceptualized in Snow Crash is much the same as the one that has evolved in recent years to accommodate networked virtual platforms. In anthropology these spaces are known as meta-places: a remix of information. Proposals like Second Life (SL), Fortnite or The Sims are already a name in the history of virtual universes, while worlds like The Sandbox, Decentraland or Axie exemplify contemporary decentralized organizations through their blockchain technology. The following contribution of ethnographic graphic story, experiential captures of virtual non-places, wants to document processes of appearance and disappearance through the image. Meanings, symbolisms, self-referentialities, ephemeral landscapes, mimesis of realities, dystopias or info-communicational disfigurements are some of the realities that hide behind each virtual creation or virtual island. Capturing these experiences in the first person over these years means approaching the logic and synergies of these meta-places. Specifically, the visual material shown is linked to the virtual world of Second Life. This metaverse constitutes one of the platforms most explored by the author, and currently retains its interaction design devised in 2003. Possibly Second Life, and its virtual peripheries, have given life to the burbclaves (isolated sites) and their social niches that Stephenson described to us, but also to a way of understanding the world inside and outside the interface.